Micellar Enhanced Spectrofluorimetric Method for the Determination of Ponatinib in Human Plasma and Urine via Cremophor RH 40 as Sensing Agent - Hany W. Darwish; Ahmed H. Bakheit; Ali Saber Abdelhameed; Amer S. AlKhairallah (International Journal of Analytical Chemistry)
An impressively simple and precise spectrofluorimetric procedure was established and validated for ponatinib (PTB) quantitation in biological fluids such as human plasma and human urine. This method depends on examining the fluorescence characteristics of PTB in a micellar system of Cremophor RH 40 (Cr RH 40). Cr RH 40 enhanced the intrinsic fluorescence of PTB distinctly in aqueous water. The fluorescence spectra of PTB was recorded at 457 nm following its excitation at 305 nm. Maximum fluorescence intensity was attained by addition of 0.7 mL of Cr RH 40 and one mL of phosphate buffer to PTB aliquots and then dilution with distilled water. There is a linear relationship between the fluorescence intensity of PTB and its concentration over the range 5–120 ngmL−1, with limit of detection and limit of quantification equal to 0.905 ngmL−1 and 2.742 ngmL−1, respectively. The accuracy and the precisions of the proposed method were checked and gave adequate results. The adopted method was applied with a great success for PTB quantitation in different biological matrices (spiked human plasma and urine) giving high recovery values.